2004
DOI: 10.1128/cdli.11.1.115-118.2004
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Seropositivity to a Major Allergen of Anisakis simplex , Ani s 1, in Dyspeptic Patients

Abstract: Finding evidence of anisakidosis requires invasive methods. We have developed a serological assay based on the detection of an immunoglobulin E (IgE) specifically directed against Ani s 1 protein, a major parasite allergen of Anisakis simplex, which has shown a high level of accuracy in the diagnosis of anisakidosis. We used this tool to determine the prevalence of anti-Ani s 1 IgE in dyspeptic patients and to investigate if its seropositivity could be related to epidemiological factors other than raw fish con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
1
15
1
1
Order By: Relevance
“…Although symptomatic anisakiasis has been reported, asymptomatic intestinal anisakiasis5 or symptomless clinical presentation9 have also been observed. Toro et al 11. suggested that human anisakiasis might be underdiagnosed in Spain because only the most severe cases that required intervention are being diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Although symptomatic anisakiasis has been reported, asymptomatic intestinal anisakiasis5 or symptomless clinical presentation9 have also been observed. Toro et al 11. suggested that human anisakiasis might be underdiagnosed in Spain because only the most severe cases that required intervention are being diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…La anisakidosis debe ser sospechada para poder realizar su diagnóstico (14,15,30) y, con toda probabilidad, está infradiagnosticada, pudiendo ser esta la causa de pacientes con síntomas dispépticos (31,32) o dolor abdominal leve (10,33). En nuestro estudio, una simple pregunta sobre la ingesta de pescado crudo ha sido muy útil, mostrando una elevada sensibilidad (98,08%) y VPN (98,39%), aunque su VPP ha sido menor (70,83%) probablemente debido al elevado consumo de pescado crudo en la población (34).…”
Section: Discussionunclassified
“…A high prevalence of seropositivity to Ani s 1 has been reported in dyspeptic patients with Helicobacter pylori infection [11], but the clinical significance of this finding is unknown. It is possible that episodes of anisakiasis in combination with H. pylori infection may have been misdiagnosed, or that the findings may reflect previous exposure to the parasite without clinical relevance.…”
Section: Introductionmentioning
confidence: 95%